Application of C-Shaped Osteotomy and Distraction Osteogenesis for Correction of Radial Angulation Deformities of the Hand in Children With Apert Syndrome: Review of 10 Years of Experience. Issue 5 (November 2015) - Vargel, Ibrahim; Calis, Mert; Cavusoglu, Tarik; Ekin, Omer; Oznur, Ali
Abstract : Abstract: Apert syndrome is characterized by short, radially deviated thumbs, leading to difficulties in daily life such as holding a fork or a spoon and buttoning up. The main goal of surgery is to achieve thumb to index finger pinch to overcome these difficulties. Seven patients (14 extremities) followed up with Apert syndrome underwent distraction after a C-shaped osteotomy to simultaneously correct the brachydactyly and the angulation deformity of the bilateral thumbs. The patients ranged in age from 4 to 7 years at the distraction operation, with a mean (SD) of 4.7 (1.7) years, and the mean (SD) length of follow-up was 100.6 (14.95) months. The mean (SD) length of the phalanges at the beginning of distraction was 19.1 (3.26) mm, and the mean (SD) length of the distracted phalanx at long-term follow-up visit was 26.2 (5.63) mm. The mean (SD) correction of radial angulation was calculated as 42.6 (9.95) degrees, and the difference was considered as being statistically significant ( P < 0.001). Minor complications such as pin loosening were observed in 6 extremities of 4 patients, and 2 patients were treated for pin tract infection. Index-to-thumb pinching was acquired by all the patients after distraction and correction of angulation. The hand features of Apert syndrome are as noteworthy as the craniofacial features and thus may lead to functional impairment and limitations in daily life. Distraction with a C-shaped osteotomy seems to be a promising method to correct both the shortness and the radial angulation of the thumb to achieve functional results.